1970
DOI: 10.1507/endocrj1954.17.131
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Properties of LATS and TSH

Abstract: LATS activity was neutralized by pretreatment of mice with anti-IgG in vivo. Simultaneous injection of epsilon-amino caproic acid and hydrocortisone does not inhibit LATS action. Human thyroid-microsomal fractions neutralize LATS activity and TSH activity. The decrease in activity of LATS and TSH caused by thyroid microsomes correlates positively. Calf thyroid microsomes are much less active than human thyroid microsomes in absorbing LATS activity. Deoxycholate and sonification solubilize the LATS neutralizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Evidence has been accumulated that LATS (Long Acting Thyroid Stimulator) may stimulate the thyroid gland in all mammalian animals (Adams 1958;McKenzie 1958;Lepp and Oliver 1967;Ochi and DeGroot 1970). For bioassay of LATS, the guinea pig or mouse has been used.…”
mentioning
confidence: 99%
“…Evidence has been accumulated that LATS (Long Acting Thyroid Stimulator) may stimulate the thyroid gland in all mammalian animals (Adams 1958;McKenzie 1958;Lepp and Oliver 1967;Ochi and DeGroot 1970). For bioassay of LATS, the guinea pig or mouse has been used.…”
mentioning
confidence: 99%
“…On the other hand, TSAb (without LATS activity) may stimulate the human, bovine and porcine thyroid but not guineapig or mouse. TSH (mammalian species) stimulates the thyroid of all animal species [10,11]. It is suggested that LATS may have thyroid stimulating (TS) activity for lower developed animals (rodents such as guinea-pig, rat and mouse) compared with TSAb (without LATS activity) [11] (Table 1).…”
Section: Latsmentioning
confidence: 99%
“…TSH (mammalian species) stimulates the thyroid of all animal species [10,11]. It is suggested that LATS may have thyroid stimulating (TS) activity for lower developed animals (rodents such as guinea-pig, rat and mouse) compared with TSAb (without LATS activity) [11] (Table 1). When TBII (with TSH receptor assay) and TSAb [CAMP production in porcine thyroid cells (PTC) assay] were determined, all LATS positive sera showed extremely high TSAb and TBII activities [12].…”
Section: Latsmentioning
confidence: 99%